Effect of the amount of ppi in polymeric foam template to the microstructure of porous porcelain produced via polymeric foam replication method - Mohd Al Amin, Muhamad Nor (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.